2017
DOI: 10.1186/s12905-017-0409-8
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of lipids, blood pressure and weight changes among premenopausal Chinese breast cancer patients after adjuvant chemotherapy

Abstract: BackgroundAdjuvant chemotherapy improves outcome of patients with early breast cancer. However, chemotherapy may be associated with long term toxicities. In this retrospective cohort study, the objectives were to determine body weight, body mass index (BMI), blood pressure and fasting lipids levels of young premenopausal Chinese breast cancer patients after adjuvant chemotherapy. Potential factors associated with these parameters were identified.MethodsEligibility criteria include premenopausal Chinese patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 45 publications
3
31
0
2
Order By: Relevance
“…In our study, weight gain ranged from 0.8 to 4.8 kg, and more than 80% of patients showed overweight after treatment. This result is similar to that found by Yeo et al 21 , who evaluated women with breast cancer and found that 52.1% of patients reached a BMI corresponding to overweight/obesity. This condition of weight gain and change in nutritional status has been widely discussed 6 , especially when it comes to weight gain in adulthood 22 , notably recognized as a risk factor for breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, weight gain ranged from 0.8 to 4.8 kg, and more than 80% of patients showed overweight after treatment. This result is similar to that found by Yeo et al 21 , who evaluated women with breast cancer and found that 52.1% of patients reached a BMI corresponding to overweight/obesity. This condition of weight gain and change in nutritional status has been widely discussed 6 , especially when it comes to weight gain in adulthood 22 , notably recognized as a risk factor for breast cancer.…”
Section: Discussionsupporting
confidence: 91%
“…Experiments have shown that a lipid is a useful biomarker for cancer diagnosis [ 63 , 64 ], especially in breast cancer. Therefore, the authors of this paper summarize the lipid molecules with diagnostic potential related to breast cancer in patients ( Table 1 ) [ 11 , 42 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Role Of Lipid In the Diagnosis Of Breast Cancermentioning
confidence: 99%
“…Anti-neoplastic therapies, in particular those that involve cytotoxic agents, are associated with short-as well as long-term adverse effects [3][4][5][6][7][8][9][10][11][12][13]. Particularly among premenopausal women, the drug's effect on ovarian function could potentially lead to long-term menstrual disruptions.…”
Section: Introductionmentioning
confidence: 99%